Identification of 5P Chromosomes in Wheat-Agropyron cristatum Addition Line and Analysis of Its Effect on Homologous Pairing of Wheat Chromosomes - Pan, Cuili; Li, Qingfeng; Han, Haiming; Zhang, Jinpeng; Zhou, Shenghui; Yang, Xinming; Li, Xiuquan; Li, Lihui; Liu, Weihua (Frontiers in Plant Science, 2022)
As an important wild relative of wheat, the P genome of Agropyron cristatum (L.) Gaertn. (2n = 4x = 28) is very valuable for wheat improvement. A complete set of wheat-A. cristatum disomic addition lines is the basis for studying the genetic behavior of alien homoeologous chromosomes and exploring and utilizing the excellent genes. In this study, a wheat-A. cristatum derivative II-11-1 was proven to contain a pair of 5P chromosomes and a pair of 2P chromosomes with 42 wheat chromosomes by fluorescence in situ hybridization (FISH) and expressed sequence tag (EST) markers analysis. Additionally, cytological identification and field investigation showed that the 5P chromosome had an effect to weaken the homologous pairing of wheat chromosome and promote the pairing between homoeologous chromosomes. This provides new materials for studying the mechanism of the alien gene affecting the homologous chromosomes pairing and promoting the homoeologous pairing of wheat. What’s more, chromosomal structural variants have been identified in the progeny of II-11-1. Therefore, the novel 5P addition line might be used as an important genetic material to widen the genetic resources of wheat.